Stabilization of Swamp Soil Using Steel Slag, Fly Ash, and Glass Bottle Powder To Determine Unconfined Compressive Strength Test (UCS) Value (Study Case on Kp. Tegal Wangi Street No.62, Rw. Arum, Sub-district Gerogol, Cilegon City, Banten) - Kusuma, Rama Indera; Mina, Enden; Fathonah, Woelandari; Handayani, Putri Nurmala (JURUSAN TEKNIK SIPIL, 2024)
Soil is an important part of construction which function as a support for the building above. Swamp soil has a soft texture and high water content, making it difficult for the soil support construction on it. The purpose of this study is to determine the soil classification based on Unified Soil Classification System (USCS) and to determine the soil characteristic by adding supplemental materials at varying percentages: 20% steel slag, 20% fly ash, and 0%, 5%, 10%, and 15% glass bottle powder, with curing periods of 0, 7, 14, and 28 days. The research findings indicated that the soil, according to the USCS classification system, falls into the OH soil classification, indicating pure clay, with a plasticity index value of 26.79%. With the addition of steel slag, fly ash, and glass bottle powder, there was a reduction in the plasticity index from 26.79% to 9.22% in variation E (20% steel slag, 20% fly ash, and 15% glass bottle powder) after a curing period of 28 days. The highest qu value was recorded in variation D (20% steel slag, 20% fly ash, and 10% glass bottle powder) after 28 days of curing, measuring 4.587 kg/cm2.